1998
DOI: 10.1007/s004020050234
|View full text |Cite
|
Sign up to set email alerts
|

Changes of sonographic, magnetic resonance tomographic, electromyographic, and histopathologic findings within a 2-month period of examinations after experimental muscle denervation

Abstract: This study compares sonographical, histopathological, magnetic resonance imaging (MRI), and electromyographical (EMG) findings following acute muscle denervation. We performed an experimental denervation of the supraspinatus and infraspinatus muscles on 35 New Zealand white rabbits by segment resection of the suprascapular nerve. The sonographical appearance of the supraspinatus muscle was followed and documented at short time intervals within a 2-month follow-up period. The sonographical, histopathological, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
7

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 0 publications
2
39
1
7
Order By: Relevance
“…A high T2 signal intensity was diagnosed in the supra-and infraspinatus muscles. This finding was corroborated by Küllmer et al's experimental study pertaining to complete suprascapular nerve section in the rabbit [35]. Küllmer et al identified an increasingly high-intensity T2-weighted signal with a peak between days 21 and 35 after nerve section.…”
Section: Muscular Edemasupporting
confidence: 73%
See 1 more Smart Citation
“…A high T2 signal intensity was diagnosed in the supra-and infraspinatus muscles. This finding was corroborated by Küllmer et al's experimental study pertaining to complete suprascapular nerve section in the rabbit [35]. Küllmer et al identified an increasingly high-intensity T2-weighted signal with a peak between days 21 and 35 after nerve section.…”
Section: Muscular Edemasupporting
confidence: 73%
“…Muscular edema may be explained by hydration modifications of the muscular mass, in the case of denervated muscles [27,33,34,35]. Signal modifications of muscles on T2-weighted images appear as early as the fifteenth day of the onset of neuropathy [34].…”
Section: Muscular Edemamentioning
confidence: 99%
“…One may assume that in terms of long-standing rotator cuff tears, two aspects, the neurogenic and the inactivity-related one, play a role in atrophy and fatty infiltration of the rotator cuff muscles. From experimental data, both phenomena are known to end in both atrophy and fatty infiltration [6,7]. The influence of both factors may possibly be individually different, leading to a more atrophic or more fatty degeneration.…”
Section: Discussionmentioning
confidence: 97%
“…In an experimental study with rabbits [6], fatty infiltration and atrophy of the supraspinatus muscle have been shown as early as 4 weeks, with a maximum at 6 weeks, after detachment of the tendon from the osseous insertion. Kullmer and colleagues [7] compared sonographical, histopathological, MRI and electromyographical findings following experimental denervation of the suprascapular nerve in a rabbit study. MRI has shown a decrease of the muscle diameter and an increased signal intensity of the muscle assessed visually after 21 days with its maximum after 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because SSN entrapment related to rotator cuff tears is thought to be a dynamic phenomenon, the co-existence of SSN neuropathy and rotator cuff tears may not always be demonstrable on EMG 11 . Magnetic resonance imaging is also helpful in identifying changes in the supraspinatus and infraspinatus muscles secondary to denervation, such as decreased muscle bulk, fatty infiltration and homogeneous high-signal intensity on T2-weighted images [37][38][39][40] . Beeler et al 37 observed the appearance of fatty infiltration and muscle atrophy on magnetic resonance imaging when comparing cases of rotator cuff tears and suprascapular neuropathy.…”
Section: Diagnostic Studiesmentioning
confidence: 99%